(untitled) - Sturgess, Kim C. (Cambridge, UK, 2004)
Kim C. Sturgess tells the story of how and why Shakespeare became a hero of American popular culture
Keywords: American literature,Văn học Mỹ; English influences,Ảnh hưởng Anh